2007
DOI: 10.2478/s11535-007-0019-9
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of tellurite resistance genes to the fitness of Escherichia coli uropathogenic strains

Abstract: Abstract:The presence of tellurite resistance gene operons has been reported in several human pathogens despite the fact that tellurium, as well as its soluble salts, are both rare in nature and are no longer in use as antimicrobial agents. We have introduced the cloned terWZA-F genes from an uropathogenic Escherichia coli isolate into another clinical E. coli isolate that was shown to be ter -gene free. The presence of the introduced genes increased the level of potassium tellurite resistance, as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 22 publications
(24 reference statements)
2
32
0
Order By: Relevance
“…Interestingly, TerD and TerE proteins were among the most abundant proteins of EHEC O157:H7 proteome (Table 1). A study performed with Uropathogenic E. coli (UPEC) isolates showed that the introduction of the ter gene cluster contributes to improve bacterial fitness inside macrophages (44). On the other hand, Yin et al (45) demonstrated that ter genes contribute to adherence of EHEC O157:H7 to epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, TerD and TerE proteins were among the most abundant proteins of EHEC O157:H7 proteome (Table 1). A study performed with Uropathogenic E. coli (UPEC) isolates showed that the introduction of the ter gene cluster contributes to improve bacterial fitness inside macrophages (44). On the other hand, Yin et al (45) demonstrated that ter genes contribute to adherence of EHEC O157:H7 to epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Although the plasmid-borne or chromosomally located ter clusters have been extensively studied, the real functions of the Te R genes are not well understood. The introduction of the ter operon from uropathogenic E. coli KL53 into non-pathogenic and uropathogenic E. coli (ter-gene free) showed that the presence of the ter loci improved the fitness of bacterial strains by enabling them to survive inside macrophages (Valkova et al 2007). Deletion of the Te R region reduced the ability of the strain to adhere to epithelial cells in vitro and in ligated pig ileal loops (Yin et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The whole determinant was cloned using in vivo methods based on the miniMu derivative cloning system, resulting in the pNT3B plasmid (Kormutakova et al 2000;Tu et al 2001;Vavrova et al 2006). The presence of the ter operon improved the fitness of bacterial strains by enabling them to escape from macrophage attack (Valkova et al 2007). In the present study, we present the biological function of the TerW protein.…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact function of this locus in vivo is not clear, orthologous genes are required for tellurite resistance in some bacteria (71)(72)(73). Tellurite is also thought to induce oxidative stress and tellurite resistance might be the result of decreased sensitivity to the oxidative stress (74).…”
Section: Tellurite Resistance Genesmentioning
confidence: 99%